Two psychological treatments for hypochondriasis. A randomised controlled trial. - Clark, D; Salkovskis, P; Hackmann, A; Wells, A; Fennell, M; Ludgate, J; Ahmad, S; Richards, H; Gelder, M (1998)
BACKGROUND: Hypochondriasis is generally considered difficult to manage. This study aimed to assess the effectiveness of cognitive therapy and to compare it with an equally credible, alternative treatment. METHOD: Forty-eight patients with hypochondriasis were initially randomly assigned to either cognitive therapy, behavioural stress management or a no treatment waiting list control group. At the end of the waiting period, patients in the control group were randomly assigned to one of the two treatments. Assessments were at pre-, mid- and post-treatment or waiting list and at three-, six- and 12-month post-treatment follow-up. RESULTS: Comparisons with the waiting list group showed both treatments were effective. Comparisons between the treatments showed that cognitive therapy was more effective than behavioural stress management on measures of hypochondriasis, but not general mood disturbance at mid-treatment and at post-treatment. One year after treatment patients who had received either treatment remained significantly better than before treatment, and on almost all measures the two therapies did not differ from each other. CONCLUSIONS: Cognitive therapy is a specific treatment for hypochondriasis. Behavioural stress management is also effective but its specificity remains to be demonstrated.